Israel's Higher Law Religion and Liberal Democracy in the Jewish State. - Mazie, Steven V. (Lanham : Lexington Books, 2006)
In Israel's Higher Law, Steven V. Mazie sheds new light on the relationship between liberalism and religion through a detailed assessment of the Jewish state. Drawing on in-depth interviews with Israeli citizens, this compelling work scrutinizes the ways in which Israelis conceptualize and debate their polity's religion-state arrangement.
Title Page; Copyright Page; Dedication; Contents; Preface: Snapshots of Israel; Acknowledgments; Introduction; Part I Foundations; 1 Beyond Separation; 2 The Jewish State; 3 Thirty-One Israelis; 4 Israel in the Eyes of Israelis; Part II Controversies Among Israeli Jews; 5 Kashrut, Shabbat and Religious Education; 6 Marriage Law; 7 Military Service; Part III Controversies Between Israeli Arabs and Jews; 8 Symbols; 9 Land; Part IV Conclusions; 10 Lessons From Israel; Appendix: Interview Guides; Bibliography; Index; About the Author.
Description based on print version record.
Keywords: Democracy -- Israel; Democracy -- Religious aspects -- Judaism; Israel -- Politics and government -- Philosophy; Judaism and politics -- Israel; Judaism and state -- Israel; Liberalism -- Israel; Liberalism -- Religious aspects -- Judaism; Judaism and state -- Israel; Judaism and politics -- Israel; Democracy -- Religious aspects -- Judaism; Liberalism -- Religious aspects -- Judaism; Israel -- Politics and government -- Philosophy; POLITICAL SCIENCE / Political Process / Political Advocacy; Electronic books